Characterization of Two Mitochondrial Genomes and Gene Expression Analysis Reveal Clues for Variations, Evolution, and Large-Sclerotium Formation in Medical Fungus Wolfiporia cocos - Chen, Mengting; Chen, Naiyao; Wu, Ting; Bian, Yinbing; Deng, Youjin; Xu, Zhangyi (Frontiers in Microbiology, 2020)
Wolfiporia cocos, a precious mushroom with a long history as an edible food and Asian traditional medicine, remains unclear in the genetic mechanism underlying the formation of large sclerotia. Here, two complete circular mitogenomes (BL16, 135,686 bp and MD-104 SS10, 124,842 bp, respectively) were presented in detail first. The salient features in the mitogenomes of W. cocos include an intron in the tRNA (trnQ-UUG2), and an obvious gene rearrangement identified between the two mitogenomes from the widely geographically separated W. cocos strains. Genome comparison and phylogenetic analyses reveal some variations and evolutional characteristics in W. cocos. Whether the mitochondrion is functional in W. cocos sclerotium development was investigated by analyzing the mitogenome synteny of 10 sclerotium-forming fungi and mitochondrial gene expression patterns in different W. cocos sclerotium-developmental stages. Three common homologous genes identified across ten sclerotium-forming fungi were also found to exhibit significant differential expression levels during W. cocos sclerotium development. Most of the mitogenomic genes are not expressed in the mycelial stage but highly expressed in the sclerotium initial or developmental stage. These results indicate that some of mitochondrial genes may play a role in the development of sclerotium in W. cocos, which needs to be further elucidated in future studies. This study will stimulate new ideas on cytoplasmic inheritance of W. cocos and facilitate the research on the role of mitochondria in large sclerotium formation.